KETERAMPILAN MOTORIK HALUS PADA ANAK KIDAL (STUDI KASUS PADA ANAK KIDAL USIA 6-7 TAHUN DI KELURAHAN MALAKA JAYA, DUREN SAWIT, JAKARTA TIMUR) - Maulina, Silvia (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2021)
This study aims to determine and describe the fine motor skills of left-handed children ages 6-7 years old, in which include eye-hand coordination skills, fingers’ flexibility, hand strength, and arms’adaptability. This research was conducted in the Malaka Jaya, Duren Sawit, East Jakarta, in May to July 2016. The method used is qualitative research case study approach. Instrument of collection data through observation, interviews, and documentation. Data analysis used is based on Miles and Huberman report of reduction data, display data and verification data. The findings of research showed that left-handed children have good eye-hand coordination, in which include the coordination between the eyes with his left hand and his right hand. Left-handed children also have good fingers’ flexibility when using tools that are made for right-handed user to create objects, like scissors. Left-handed children have a greater strengthat left hand than right hand. Left- handed children have good adaptation in activities that are ethically deminding the use of the righ hand and manipulating objects that are made for right-handed users. At the imitation stage of left-handed children are retaining their own attitude when undertaken the activities though models using right-hand dominance.